Boosting electrocatalytic nitrogen reduction to ammonia in alkaline media. (29th June 2021) - Li, Guangzhe; Lin, He; Pan, Zhefei; Liu, Yun; An, Liang
Summary: Electrochemical ammonia synthesis is a promising alternative technique to traditional Haber‐Bosch process, capable of converting nitrogen to ammonia at ambient conditions and can be driven by intermittent energy. However, it generally requires high overpotential for nitrogen dissociation due to the stable triple bonds of nitrogen molecules, resulting in a poor ammonia yield rate. Tailoring the electrolyte‐ion composition is a promising approach to facilitate nitrogen dissociation by optimizing the local reaction environment near the electrode toward ammonia production. In this study, the effect of anions in the electrolyte composition on electrocatalytic nitrogen reduction to ammonia is investigated. It is found that a lower onset potential for nitrogen reduction (−0.2 V vs RHE) and a higher ammonia yield rate (6.69 × 10 −11  mol cm −2  s −1 ) are achieved in the electrolyte containing OH − anions, compared to singly charged anions of Cl − and SCN − when using an electrode made of commercial Au/C electrocatalysts. In addition, current density contributed by nitrogen reduction achieved in the high‐pH electrolyte (pH ≥ 13) shows around 3‐fold increase compared to that in low‐pH electrolyte (11 ≤ pH ≤ 12). Such performance enhancement is possibly attributed to the appearance of hydronium ions (H3 O + ) in high‐pH electrolyte, which facilitates nitrogen dissociation by strengthening protonation( * N 2 + 6 H 3 O + + 6 e − → * + 2 NH 3 · H 2 O + 4 H 2 O ). Abstract : The appearance of hydronium ions in alkaline media facilitates nitrogen reduction to ammonia by strengthening protonation (*N2  + 6H3 O +  + 6e −  → 2NH3 ·H2 O + 4H2 O).